ANALYSIS OF ORGANIZATIONAL COMMITMENT AND EMPLOYEE PERFORMANCE PT. HWA SEUNG - Putra, Febrianur Ibnu Fitroh Sukono; Ingsih, Kusni; Saputra, Robby Maulana (2021)
As an effort to achieve a high organizational performance, the main thing that must be owned is quality human resources. To obtain this, employees must have the ability and skills to support the completion of work ranging from intrinsic motivation to empowerment programs and the availability of a good work environment. So this research aims to analyze the organizational commitment and performance of the employees of PT. Hwa Seung Jepara. This study uses quantitative methods with the population are employees of PT. Hwa Seung. The sampling technique in this research was carried out by proportional random sampling technique. The type of data in this research is primary data obtained directly from respondents. The data collection method used was a field survey in the form of distributing and filling out individual questionnaires. The analytical tool used in this research is path analysis. The results of this research include empowerment, work environment, and intrinsic motivation which have a positive significant effect on organizational commitment and employee performance. Organizational commitment variables are able to mediate the relationship between the influence of empowerment, work environment, and intrinsic motivation on employee performance.